Comparison of bispectral index targeted end-tidal concentration of desflurane during three phases of orthotopic liver transplantation - Kumar, Gyanendra (Indian J Anaesth, 2019)
BACKGROUND AND AIMS: Reduced inhalational anaesthetic requirement in end-stage liver disease during living donor orthotopic liver transplantation (LD-OLT) is due to increased endogenous opioids. This study evaluated the changes in bi-spectral index (BIS) monitored end-tidal desflurane (ET(Des)) requirements during ‘dissection’, ‘anhepatic’, and ‘neohepatic’ phases of LD-OLT. METHODS: This prospective, cohort study included 40 adults undergoing LD-OLT under general anaesthesia (GA). All patients received BIS-guided desflurane GA. ET(Des) requirements in three phases of LD-OLT (primary objective); relationship between inhalational anaesthetic requirements and severity of liver disease; and effect of changes in mean arterial pressure (MAP) and body temperature on ET(Des) concentration for all three phases were also evaluated. RESULTS: ET(Des) during the ‘dissection’ phase (2.92 ± 0.65%) was > ‘anhepatic’ (2.68 ± 0.85%, P = 0.049) and ‘neohepatic’ phases (2.58 ± 0.71%, P = 0.005). Patients with model of end-stage liver disease (MELD) score < 20 returned significantly greater ET(Des) than those with MELD score ≥20 during the ‘dissection’ (MELD <20: 3.11 ± 0.49%; MELD ≥20: 2.58 ± 0.77%, P = 0.01) and ‘anhepatic’(MELD <20: 2.96 ± 0.76%; MELD ≥20: 2.17 ± 0.79%, P = 0.003) phases. A positive correlation was observed between ET(Des)(r = 0.584, P = 0.001) and temperature in the ‘dissection’ phase only. CONCLUSION: In patients undergoing LD-OLT, BIS monitoring guidance of depth of desflurane GA suggests lower desflurane requirements during ‘anhepatic’ and the ‘neohepatic’ phase of surgery. Also, the desflurane requirement is greater in patients with lesser severity of liver disease.